Barriers to switching in retail electricity markets: A regional analysis of the Italian market. - Fontana, Magda; Iori, Martina; Nava, Consuelo Rubina (Springer, 2018)
The paper analyzes the determinants of switching barriers in a sample of Italian households. Inertia, while depressing consumer engagement and the associated benefits, also reduces competitive pressure in the energy retail free market. After the liberalization of the energy retail market in the European Union, the observed switching rates are relatively low: Identifying the causes of consumer inertia is therefore crucial to achieve the goals set by the European Union in the Three Energy Packages. We use a logistic regression model to discover the causes of consumer inertia as listed in the Aspect of Daily Life Survey (ISTAT 2014). Namely, we take into account: (i) loyalty, (ii) lack of information, (iii) difficulties in evaluating the economic benefits deriving from switching, (iv) perception of small savings from switching and (v) concerns for a worsening of the quality of service in case of switching. The main findings relate awareness - knowledge of the possibility to change the retailer - to the level of education and to the frequency of internet use. In addition, we find that households that are different in numerosity, geographical and urban location and in economic resources tend to attribute inertia to different causes. Among these, the most frequently reported are alleged difficulties in comparing offers and concerns about lower quality of service.
Keywords: Energiepolitik; Energieversorgung; Energiemarkt; Verbraucher; Preisvergleich; Wirtschaftsgut